- Download PDF
1 Answer | Add Yours
You need to remember the complex number theory telling that `i=sqrt(-1), i^2=-1,i^3=-i,i^4=1` .
Notice that the product contains the factor `(1-i^4), ` hence plugging `i^4=1` in `1 - i^4` yields 1 - 1 = 0.
Since the factor `(1-i^4) = 0` , this factor cancels all product, hence `(1-i)(1-i^2)(1-i^3)...(1-i^2008) = 0.`
Hence, evaluating the product yields `(1-i)(1-i^2)(1-i^3)...(1-i^2008) = 0.`
We’ve answered 324,123 questions. We can answer yours, too.Ask a question